Pimenta pseudocaryophyllus Derivatives: Extraction Methods and Bioactivity Against Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) - Ribeiro, L. P.; Ansante, T. F.; Niculau, E. S.; Pavarini, R. [UNESP]; Silva, M. F.G.F.; Seffrin, R. C.; Vendramim, J. D. (Springer Nature, 2015)
Plant-based insecticides can play an important role in integrated insect pest management (IPM), especially in protecting stored grains. The aim of this study was to evaluate the bioactivity of derivatives (powder, ethanolic extract, and essential oil (EO)) from the leaves of Pimenta pseudocaryophyllus (Myrtaceae), a Brazilian native species, against Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae), the main insect pest of stored corn. The powder and essential oil prepared from leaves showed a repellent effect. Moreover, the EO exhibited promising insecticidal activity through residual contact (LC50 = 1522 mg kg−1) and significantly decreased the F1 progeny and the percentage of damaged grains. However, the essential oil obtained from P. pseudocaryophyllus leaves did not result in significant mortality of S. zeamais adults after 72 h of exposure by fumigation in concentrations up to 400 μL L−1 of air. Based on GC-MS analysis, 20 compounds were identified in the essential oil of P. pseudocaryophyllus leaves, being chavibetol (38.14%), methyl eugenol (11.35%), and terpinolene (9.17%) as the major constituents. Essential oil from P. pseudocaryophyllus leaves is an interesting source of compounds with grain-protectant properties and should be analyzed in future studies aiming to develop new bioinsecticides to use in the IPM of stored grains.
Keywords: Chavibetol; essential oil; insecticidal activity; maize weevil